Development of a Community Participation Index as an Environmental Health Effort in Control Dengue Hemorrhagic Fever in Surabaya - Muhammad Farid Dimjati Lusno; Siti Zubaidah; Ririh Yudhastuti; Hari Basuki Notobroto; Muhammad Rifqo Hafidzudin Farid; Abdul Fattah Farid; Rahmat bin Dapari (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Dengue haemorrhagic fever (DHF) remains a critical public health challenge in Surabaya, Indonesia. Despite intensive efforts, standardized measures for assessing community involvement in DHF control are lacking. This study addresses the gap by developing a Community Participation Index (CPI) that encompasses 3M Plus actions (drain, cover, recycle water containers plusother preventive actions), opportunities, and collective action at the household level, providing a comprehensive, quantitative tool to evaluate and guide intervention strategies. Methods: An analytical observational case-control design was conducted, involving 1,880 households, selected through stratified random sampling from 47 health centers across diverse epidemiological and demographic zones. Data collection included structured questionnaires, household interviews, and direct observation, with validity and reliability ensured by Cronbach alpha 0.74 and confirmatory factor analysis (CFA). The “One House One Jumantik” program, introduced nationally since 2016 and locally in Surabaya since 2017, served as a focal intervention to increase active community monitoring and participation. Results and Discussion: The CPI model demonstrated satisfactory fit (CFI 0.92, RMSEA 0.06), with opportunity and collective action recognized as the strongest contributors. The implementation of “One House One Jumantik” correlated with increased engagement and improved 3M Plus practices, resulting in lower DHF incidence. Biases related to sampling and self-reporting weremitigated through careful design and data triangulation. Conclusion: The CPI offers significant practical value for DHF surveillance, targeted interventions, and policy formulation. Strengthening ongoing education, improving access, and adapting programs to local contexts are essential for bridging gaps between awareness and sustainable action.